THE STUDY ON THE RESISTANCE SPOT WELDING OF DISSIMILAR MATERIALS OF STAINLESS STEEL 316L AND TI-6AL-4V TITANIUM ALLOY WITH THE INTERLAYER OF ALUMINUM ALLOY - TAUFIQURRAHMAN, IQBAL (2021)
Nowadays, there has been a fast-growing concern in using alternative and hybrid materials in the automotive and aerospace industries that have the characteristics of lightweight material, good corrosion resistance, and good weldability